Design, build and demonstration of a fast, reliable portable phosphate field analyser. (December 2021) - O'Grady, Joyce; Kent, Nigel; Regan, Fiona
Abstract: A fully integrated lab-on-a-disc sensor for multi-sample phosphate detection based on the molybdenum blue method for the determination of soluble reactive phosphorus in surface waters is demonstrated. An adapted and simplified molybdenum blue method which eliminates a number of steps previously associated with the detection of phosphate in environmental samples is utilised in this sensing device. The modified method facilitates the on-board storage of reagents in the microfluidic device for the determination of phosphate over a linear range of 54–600 μg/L, with a limit of detection of 16 μg/L phosphate. Validation of the fully integrated device was analysed using environmental river samples and by carrying out a spiked matric analysis. The system is comprised of a lab-on-a-disc microfluidic disc and platform that allows the disc to centrifugally spin, allowing for sample and reagent to mix, also facilitating the manipulation of fluids from one chamber to another for detection. The detector in the system is made up of a low-cost optical transducing pair (light emitting diode (LED) and a photodiode (PD). This integrated system presents a simple, cost effective and near real-time method for the direct analysis of phosphate in surface water.